Desire and violence in modern sport - Sakamoto, T. (International Journal of Sport & Health Science, 2017)
Why do we want to win in a sport as strongly as we do? This paper explored this question from the point of view of desire in an attempt to delineate how desire manifests in modern sports, as well as its relevance to brutality. A great many incidents that occur in real life teach us that modern sports involve a great deal of violence. It is equally clear that no violent behaviour will happen in a situation where no competition exists. As we confirmed at the outset, competitors are bound to have an essential desire to win in sports competitions. This desire is directed towards an object called victory. According to Girard, the desire to win is anything but autonomous; rather, it exists as the mimicry of another person's desire. When revisiting modern sports from the point of view of theory of desire in this manner, we can see that international megaevents such as the Olympics, the world cups of various sports, etc., propagate our desire to win to a formidable degree. In other words, modern sports are intimately connected with capitalist economies and strengthen triangular desire in a synergistic manner. The strengthened desire lacks an outlet, reaches the hell of reciprocal mediation, and consequently manifests as brutality.